The in vitro metabolism of norcotinine and related biotransformation products by microsomal preparations - (:unkn) unknown (MEDECINE ET HYGIENE, 1997)
Since norcotinine and 4-(3-pyridyl)-4-oxobutyramide (POBAM) are probable metabolites of nicotine and cotinine, it was of interest to investigate the further in vitro metabolism of these compounds. We now report our preliminary findings using rat microsomal preparations (induced and/or non-induced with phenobarbitone) fortified with NADPH. Following norcotinine metabolism, two compounds, i.e. the corresponding ketoamide (POBAM) and another product, were detected. The latter metabolite has an identical HPLC retention time as that of nicotinamide. Both metabolites showed identical UV spectra when compared to authentic compounds using a multi-array UV detector linked to a HPLC system. The structures of these metabolites were also confirmed by mass spectral analyses. The amount of POBAM was significantly increased when phenobarbitone induced rat microsomes was used. It indicates that the ketoamide is formed via a phenobarbitone inducible isozyme of CYP450. Following the metabolism of POBAM, two compounds, i.e. the corresponding acid (POBA) and an unidentified product, were detected. The uncharacterised compound had an identical HPLC retention time as nicotinamide. Both metabolites gave a UV spectrum identical to the authentic compounds. The detection of nicotinamide in incubates of norcotinine and POBAM suggests that it is released from NADP(H) by a stimulatory effect on glycohydrolase by the substrates. Further studies on the enzymology of these processes are in progress.
Keywords: nicotinamide; norcotinine; POBAM; NADP(H); glycohydrolase